Characterizing IT asset disposition flows for the circular economy: A case study on export for reuse from Ireland - Kathleen McMahon; Chidinma Uchendu; Colin Fitzpatrick (Journal of Industrial Ecology, 2023)
Understanding flows of resource‐rich electrical and electronic equipment throughout its life cycle is increasingly important in the development of global circular economies, reflected by heavy legislative focuses on waste prevention and resource use efficiency. This research facilitates broader material flow analysis by characterizing flows of professional IT equipment within the Republic of Ireland, emphasizing the flow of legal exports for the purposes of refurbishment and reuse. The analysis of transboundary movement of non‐waste used equipment contributes to a less often measured, but influential, facet of material flows. Eight key exporters of used equipment, comprising original equipment manufacturers, information technology asset disposition companies, and waste treatment facilities, were interviewed to characterize the sector, map the flow of materials, and identify gaps in existing reporting. Interviewed organizations declared exports of used equipment by category using a voluntary declaration form. Two key flows were identified representing currently unreported and unmeasured flows of non‐waste professional equipment. A total of 441,261 units of equipment were declared to be exported for reuse from the Republic of Ireland through these previously unmeasured flows in 2019. Product keys developed by United Nations University were used to estimate the weight of total units exported as approximately 576 metric tons, amounting to an additional approximately 9% of the weight of IT equipment collected in the Republic of Ireland in 2018, or 0.1 kg per inhabitant. These quantifications of IT equipment exported for reuse will be a key component of future material flow analyses in the development of a circular economy.